Answer:
A. 3s
Step-by-step explanation:
The height of the object after t seconds is given by:
![h(t) = -16t^2 + 144](https://tex.z-dn.net/?f=h%28t%29%20%3D%20-16t%5E2%20%2B%20144)
When will the object hit the ground?
It hits the ground after t seconds, and t is found when
. So
![h(t) = -16t^2 + 144](https://tex.z-dn.net/?f=h%28t%29%20%3D%20-16t%5E2%20%2B%20144)
![0 = -16t^2 + 144](https://tex.z-dn.net/?f=0%20%3D%20-16t%5E2%20%2B%20144)
![16t^2 = 144](https://tex.z-dn.net/?f=16t%5E2%20%3D%20144)
![t^2 = \frac{144}{16}](https://tex.z-dn.net/?f=t%5E2%20%3D%20%5Cfrac%7B144%7D%7B16%7D)
![t^2 = 9](https://tex.z-dn.net/?f=t%5E2%20%3D%209)
![t = \sqrt{9}](https://tex.z-dn.net/?f=t%20%3D%20%5Csqrt%7B9%7D)
![t = 3](https://tex.z-dn.net/?f=t%20%3D%203)
3 seconds, so the correct answer is given by option a.
Answer:
y = 3
x = 2
Step-by-step explanation:
-5x + 4y = 2
9x - 4y = 6
Sum both eq.
-5x + 9x = 4x
+4y - 4y = 0
2 + 6 = 8
then:
4x + 0 = 8
4x = 8
x = 8/4
x = 2
from the first eq.
-5x + 4y = 2
-5*2 + 4y = 2
-10 + 4y = 2
4y = 2 + 10
4y = 12
y = 12/4
y = 3
Check:
from the second eq.
9x - 4y = 6
9*2 - 4*3 = 6
18 - 12 = 6
Answer:
the common difference is plus 3
Answer:
-5 and 17
Step-by-step explanation:
The sum of two numbers (let's just say number a and number b) is 12.
a + b = 12
The difference between the same two numbers (still a and b) is 22.
b - a = 22
(Move variable a to the right side to get the following.)
b = 22 + a
(This way, we can substitute b = 22 + a into the first equation, a + b = 12, and solve.)
a + (22 + a) = 12
a + a + 22 = 12
2a = -10
a = -5
a + b = 12
-5 + b = 12
b = 17